Limited gene exchange between two sister species of leaf beetles within a hybrid zone in the Alps. (28th September 2019) - Kastally, Chedly; Trasoletti, Marta; Mardulyn, Patrick
Abstract: Analysing genomic variation within and between sister species is a first step towards understanding species boundaries. We focused on two sister species of cold‐resistant leaf beetles, Gonioctena quinquepunctata and G. intermedia, whose ranges overlap in the Alps. A previous study of DNA sequence variation had revealed multiple instances of mitochondrial genome introgression in this region, suggesting recent hybridization between the two species. To evaluate the extent of gene exchange resulting from these hybridization events, we sampled individuals of both species inside and outside the hybrid zone and analysed genomic variation among them using RAD‐seq markers. Individual levels of introgression in the nuclear genome were estimated first by defining species‐specific SNPs (displaying a fixed difference between species) a priori and second by using model‐based methods. Both types of analyses indicated little gene exchange, if any, between species at the level of the nuclear genome. Whereas the first method suggested slightly more gene flow, we argue that it has likely overestimated introgression in the phylogeographic context of this study. We conclude that strong intrinsic barriers prevent genetic exchange at the level of the nuclear genome between the two species. The apparent discrepancy observed between introgression occurring in the nuclear and mitochondrial genomes could be explained by selection acting in favour of the latter. Also, these results have consequences for the phylogeographic study of each species, since we can assume that genetic diversity in the overlapping portion of their ranges is not the product of introgression. Abstract : Following a prior study that revealed extensive mitochondrial genome introgression between two sister species of leaf beetles in the Alps, suggesting recent hybridization, we sampled individuals inside and outside this hybrid zone and analysed their genomic variation using RADseq markers. Contrary to what was found for mitochondrial markers, little, if any, genetic exchange was highlighted in the nuclear genome, suggesting strong intrinsic barriers to reproduction between the two species.